Long-Term Stability for Co-Electrolysis of CO2/Steam Assisted by Catalyst-Infiltrated Solid Oxide Cells - Jeong, Hyeon-Ye; Yoon, Kyung Joong; Lee, Jong-Ho; Chung, Yong-Chae; Hong, Jongsup (한국세라믹학회, 2018)
This study investigated the long-term durability of catalyst(Pd or Fe)-infiltrated solid oxide cells for CO2/steam co-electrolysis. Fuel-electrode supported solid oxide cells with dimensions of 5 x 5 cm(2) were fabricated, and palladium or iron was subsequently introduced via wet infiltration (as a form of PdO or FeO solution). The metallic catalysts were employed in the fuel-electrode to promote CO2 reduction via reverse water gas shift reactions. The metal-precursor particles were well-dispersed on the fuel-electrode substrate, which formed a bimetallic alloy with Ni embedded on the substrate during high-temperature reduction processes. These planar cells were tested using a mixture of H2O and CO2 to measure the electrochemical and gas-production stabilities during 350 h of co-electrolysis operations. The results confirmed that compared to the Fe-infiltrated cell, the Pd-infiltrated cell had higher stabilities for both electrochemical reactions and gas-production given its resistance to carbon deposition.